Exploring young professionals' hesitation to joint German public health service – a mixed method study. (30th September 2020) - Stratil, J; Arnold, L
Abstract: Background: The "Öffentliche Gesundheitsdienst (ÖGD)" is the central public health institution in Germany. The ÖGD comprises of all public sector institutions responsible for protecting and monitoring the population health on the federal, state, county and municipal level. Its key functions contain identifying and addressing public health threats, and promoting the heath of the general population. Despite the important role, the ÖGD has not been successful in attracting and recruiting young professionals; a situation aggravated by an expected wave of retirements. We aimed to identify barriers and discuss solutions to promote the attractiveness of working in the German public health service among young professionals. Methods: Firstly, we conducted a theory-based online-survey of medical and public health students enrolled in Germany. Secondly, we conducted key-informant interviews with a purposive sample of former public health students meanwhile working at the local health authority or a public health department as well as leading persons in the same institutions. Results: In the survey of more than 2400 students, among others identified barriers included: students not being aware of the ÖGD and its activities, negative images of the ÖGD, and unattractive job profiles. In the interviews, some participants expressed or experienced a strong preference within the ÖGD to attract medical students to the detriment of public health students. A lack of appreciation and strictly hierarchical work contexts were identified as further obstacles. Conclusions: The survey and interviews identified several potential barriers and obstacles for young professionals to join the public health workforce in Germany. Likely, major reforms within the ÖGD as well as in the education of medical and public health students is necessary to overcome this challenge. The results of the qualitative study identify several potential solutions for improvement. Key messages: We conducted a mixed-method study of medical and public health students and young professionals to explore the challenges of the German public health service to attract young professionals. Our study shows that major reforms are likely necessary to increase the attractiveness of the German public health service.